MXCuBE2: the dawn of MXCuBE Collaboration. (22nd February 2019) - Oscarsson, Marcus; Beteva, Antonia; Flot, David; Gordon, Elspeth; Guijarro, Matias; Leonard, Gordon; McSweeney, Sean; Monaco, Stephanie; Mueller-Dieckmann, Christoph; Nanao, Max; Nurizzo, Didier; Popov, Alexander N.; et al.
Abstract : The collaboration for the development of MXCuBE2 control software for Macromolecular Crystallography beamlines is described Abstract : MXCuBE2 is the second‐generation evolution of the MXCuBE beamline control software, initially developed and used at ESRF – the European Synchrotron. MXCuBE2 extends, in an intuitive graphical user interface (GUI), the functionalities and data collection methods available to users while keeping all previously available features and allowing for the straightforward incorporation of ongoing and future developments. MXCuBE2 introduces an extended abstraction layer that allows easy interfacing of any kind of macromolecular crystallography (MX) hardware component, whether this is a diffractometer, sample changer, detector or optical element. MXCuBE2 also works in strong synergy with the ISPyB Laboratory Information Management System, accessing the list of samples available for a particular experimental session and associating, either from instructions contained in ISPyB or from user input via the MXCuBE2 GUI, different data collection types to them. The development of MXCuBE2 forms the core of a fruitful collaboration which brings together several European synchrotrons and a software development factory and, as such, defines a new paradigm for the development of beamline control platforms for the European MX user community.